Dr. Andries Albertus Odendaal Snr., evangeliedraer in 'n multi-dimensionele konteks. 'n Kort historiese oorsig en sendingkundige evaluering van sy lewe en werk (Deel 1) - P. Robinson (Acta Theologica)
The events in Parts 1 and 2 of this article cover the period from July 1917 to April 2004. Part 1 briefly introduces the life and work of a so-called “local missionary” of the Dutch Reformed Church in South Africa. The advantage of such an autobiographical approach is that it unlocks valuable information, which would otherwise be passed unnoticed, leaving an incomplete if not skewed portrayal of some developments in the past. Part 1 discusses the following aspects: The hardships of life on a small farm in South Africa during the 1920s and 1930s; the difficulty in obtaining thorough school education; the demands of training as a DRC missionary; challenges of running a so-called “mission congregation” within the same geographical borders as the sending church or churches; language acquisition in multi-language situations, and the lonely road of improving academic qualifications.